From Negative Aspects and Black Aspects of Vietnam Education to Lessons for Social Sciences Students - Dinh Tran Ngoc Huy; Pham Thi Hong Nhung; Ly Thi Hue; Ly Lan Yen; Nguyen Anh Thu; Dinh Tran Ngoc Hien (Borong Newinera Publisher, 2022)
In our research, we level strong criticism at the State Professor Council in Vietnam, using the case of Tran Van Tho and other members as a representative illustration of their efforts to impede or restrict the growth of the nation's scientific community. We also do not place enough importance on the publication of bogus news online by various Vietnam publications (Thanhnien.vn and Tuoitre.vn), despite the fact that it may lead to confusion, as well as problems and concern in the community. In addition, we oppose the excessive tuition fees and other expenses that have been imposed by Banking University HCM city Vietnam and other institutions in HCM city in recent years, which have caused difficulties for families, parents, students, and society as a whole. In addition, we use these problematic aspects of the education system in Vietnam as a case study to instruct students majoring in social sciences. After that, the authors apply a strategy based on the laws of Malaysia in order to solve the problem of fake news published in the newspapers tuoi tre and thanh nien in Vietnam throughout the period 2015-2022. After the case discussion that was offered earlier, the authors assess the opinions of President Ho Chi Minh on publishing activities for the purpose of better teaching pupils. This is not the least of the authors' contributions.